2017
DOI: 10.1002/jmri.25669
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics assessment of bladder cancer grade using texture features from diffusion‐weighted imaging

Abstract: Purpose To 1) describe textural features from diffusion-weighted images (DWI) and apparent diffusion coefficient (ADC) maps that can distinguish low-grade bladder cancer from high-grade one, and 2) propose a radiomics-based strategy for cancer grading using texture features. Materials and Methods 61 patients with bladder cancer (29 in high- and 32 in low-grade groups) were enrolled in this retrospective study. Histogram- and gray-level co-occurrence matrix (GLCM)-based radiomics features were extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
135
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 30 publications
3
135
2
Order By: Relevance
“…Recently, the term radiomics has drawn attention in medical image research, which has two important aspects: 1) many quantitative features extracted from medical images that represent structural, physiopathologic, and genetic characteristics; and 2) machine‐learning models to deal with these image features and produce clinically significant output. So far, promising results have been obtained in many cancer studies based on the radiomics strategy, but few of these studies were conducted for glioma grading . Ryu et al and Brynolfsson et al reported that the gray‐level co‐occurrence matrix (GLCM)‐based texture features derived from DWI and corresponding apparent diffusion coefficient (ADC) maps of glioma patients could be used to represent a set of discriminative image patterns automatically, suggesting that GLCM texture features analysis may be a useful tool for glioma grading and prognosis prediction.…”
mentioning
confidence: 99%
“…Recently, the term radiomics has drawn attention in medical image research, which has two important aspects: 1) many quantitative features extracted from medical images that represent structural, physiopathologic, and genetic characteristics; and 2) machine‐learning models to deal with these image features and produce clinically significant output. So far, promising results have been obtained in many cancer studies based on the radiomics strategy, but few of these studies were conducted for glioma grading . Ryu et al and Brynolfsson et al reported that the gray‐level co‐occurrence matrix (GLCM)‐based texture features derived from DWI and corresponding apparent diffusion coefficient (ADC) maps of glioma patients could be used to represent a set of discriminative image patterns automatically, suggesting that GLCM texture features analysis may be a useful tool for glioma grading and prognosis prediction.…”
mentioning
confidence: 99%
“…Based on these findings above, we hypothesized that: 1) the radiomics features extracted from preoperative mpMRI to characterize the subtle variations of tissue distribution within the lesion might be potential in predicting BCa recurrence; 2) the combination of the radiomics strategy with important clinical factors, mainly including age, gender, histological grade, and MIS of the archived tumor with the maximal size in bladder lumen, tumor size, NoT, operation choice, together with the imaging signs like stalk and SLE, might add the incremental value for TFTY BCa prediction.…”
mentioning
confidence: 99%
“…The radiomics process usually requires: 1) large amounts of image features from medical images which could reflect structural, physiopathologic, and genetic information; and 2) machine‐learning models for excavating implicit clinical values of these image features. So far, many oncologic radiomics studies have yielded promising results . Specifically, radiomics features have been reported to be useful tools for glioma grading or prognosis prediction .…”
mentioning
confidence: 99%